Effect of therapeutic methods and exercises for the rehabilitation of low lumbar herniated disc in the infected (30-40) years - Rana Qais Dr. Warda Ali (الرياضة المعاصرة)
The aim of the research is to prepare training exercises with therapeutic and rehabilitative methods for the slight lumbar herniated disc for the injured (30-40) years as well as the impact of the rehabilitation exercises with therapeutic and rehabilitative means of the slight lumbar herniated disc for the infected (30-40) years, and the researchers used the curriculum The one-group demo identifies the research community with the patients with the simple herniated disc and a number of the injured and the number of (3) injured reviewers of the center of Specialty, orthopedic surgery and fractures and paragraphs/Harithiya The researchers concluded that the therapeutic methods have achieved positive results in Rehabilitation of the injured and a clear increase in the flexibility of the muscles of the back the flexibility is very important for people with spinal slide improves the low level of pain in the research sample, which indicates that the injured have achieved good results in the therapeutic exercises and recommended the researchers to use the means Therapeutic used in research the researchers are recommending that the patients be given prompt and appropriate treatment and rehabilitation as soon as the pain or feeling of the injury occurs